Flexible zinc electrodeposition method adaptive to green power supply

By using weak solvation additives and time-dividing current density jump-changing electroplastic method during zinc electroplastic process, the problems of low zinc electroplastic efficiency and high energy consumption caused by green electricity supply volatility are solved, and the uniformity and stability of zinc deposition are achieved, energy consumption is reduced and green and low-carbon transformation is promoted.

CN120291160APending Publication Date: 2025-07-11CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510461144.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-14
Publication Date
2025-07-11

AI Technical Summary

Technical Problem

In the prior art, under the volatility of green electricity supply, there are problems such as low current efficiency, high energy consumption and uneven zinc deposition during the zinc electrostatic deposition process. It is difficult for traditional additives to achieve rapid deposition and stability of zinc under high current density.

Method used

The zinc sulfate solution containing weak solvation additives is used as the electrolyte solution, and combined with the time-dividing current density jump electrolysis method, the electrolyte structure and current density are regulated, and the hydrogen evolution side reaction is suppressed, and the uniform deposition of zinc is promoted.

Benefits of technology

Under the conditions of fluctuation in green electricity supply, the current efficiency of zinc electrodistribution and energy consumption are significantly improved, while improving the uniformity and stability of zinc deposition and reducing carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120291160A_ABST
    Figure CN120291160A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible zinc electrodeposition method adaptive to green power supply, which comprises the following steps: taking a zinc sulfate solution containing a weak solvation additive as an electrolyte, and adopting time-phased current density jump type electrodeposition according to the difference of a green power supply peak period, a green power supply stable period and a green power supply valley period, and gradient current density electrodeposition is adopted during mutual switching of the power supply peak period, the green power supply stable period and the green power supply valley period. The weak solvation additive improves a zinc ion solvation structure, inhibits hydrogen precipitation, promotes uniform and rapid discharge of zinc ions on the surface of an electrode, and improves the stability of a cathode in the zinc electrodeposition process with green electricity power supply volatility, so that the current efficiency of the zinc electrodeposition flexible production process under wide load fluctuation is improved, and the service life of the cathode is prolonged. And the uniformity of zinc deposition is greatly improved while the power consumption is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of zinc electrowinning in hydrometallurgical zinc production, and particularly relates to a flexible zinc electrowinning method adapted to green power supply. Background Art

[0002] Currently, about 90% of the global total zinc production is produced by hydrometallurgical zinc production, and the costs and energy consumption of the zinc electrowinning process account for 30% and 80% of the entire hydrometallurgical process respectively. In production, a constant current density of 400 - 450 A / m 2 is often used for electrodeposition. The actual energy consumption reaches 3000 - 3500 kWh / t, about twice the theoretical energy consumption (1600 kWh / t), and the current efficiency is only 82 - 90%. According to statistics, the total carbon emission of smelting production per ton of zinc is about 5.19 tons, of which the carbon emission of electricity consumption can reach about 2.19 tons. It can be seen that the carbon emissions in the zinc smelting process mainly come from energy consumption. To accelerate the carbon reduction process, "green power" mainly generated by renewable energy such as wind and light will become the main body of energy consumption. However, the problems such as seasonal imbalance and unpredictability of energy in the new energy power system, which cause the volatility of power supply, will reduce the stability of the electrolytic cell operation, making the surface of the electrowon zinc sheet uneven. Therefore, it is necessary to coordinate the zinc electrowinning current density to improve the adaptability of the electrolytic cell operation and adapt to the flexible, stable and efficient zinc electrowinning driven by green power.

[0003] Under such a flexible power supply system, challenges such as low current efficiency, high energy consumption, and poor zinc product quality caused by hydrogen evolution side reactions at low current density and uneven zinc deposition at high current density will be faced. By methods such as the zinc / acid ratio in the electrolyte, adding surfactants, leveling agents, etc., the hydrogen evolution side reaction can be inhibited to a certain extent and the uniform deposition of zinc can be promoted. However, the additives used mainly form an adsorption layer by adsorbing on the cathode surface to inhibit the direct contact between the electrolyte and the electrode while improving the nucleation behavior of zinc, thereby improving the electrical efficiency and energy consumption. Due to the strong interaction with the electrode surface, it limits the rapid deposition of zinc at high current density, increases the cathode polarization, reduces the current efficiency and increases the power consumption.

[0004] In addition, Chinese Patent CN105937040A discloses a process for reducing the direct current unit consumption of cathode zinc in the hydrometallurgical zinc smelting of high-impurity ore. Although the current efficiency is improved, the process is complex, and the added manganese powder may reduce the purity of electrolytic zinc. Chinese Patent CN117779112A reduces the direct current consumption of zinc electrowinning by regulating the mixing ratio of fresh electrolyte and waste liquid. The process is simple, but it is only applicable to the constant current electrowinning process at 400 - 500 A / m 2 below.

[0005] Regulating the electrolyte composition is an effective method to improve the current efficiency of zinc electrowinning, reduce energy consumption and improve the quality of zinc products. In particular, the use of additives has obvious effects and is simple and easy to implement. However, due to the single efficacy of additives, the improvement of the zinc electrowinning process is limited, and it is only applicable to the constant current electrodeposition process at low current densities. To solve the problems of deteriorated electrolysis indexes caused by the flexible operation of electrolytic cells due to the power supply volatility brought by green electricity, it is still necessary to develop an electrolyte composition suitable for the fluctuations of the wide-load electrolysis process. Summary of the Invention

[0006] Aiming at the problems in the prior art, such as low current efficiency, high energy consumption, and poor zinc quality caused by hydrogen evolution and uneven zinc deposition due to the volatility of green electricity supply, the purpose of the present invention is to provide a flexible zinc electrowinning method suitable for green electricity supply. This method uses a zinc sulfate solution containing a weakly solvating additive as the electrolyte, which inhibits the hydrogen evolution side reaction while accelerating the desolvation process of zinc on the electrode surface, and improves the stability of the cathode during the zinc electrowinning process with the volatility of green electricity power supply. The process of stepwise current density jump electrodeposition is adopted to greatly improve the uniformity of zinc deposition while saving energy consumption.

[0007] To achieve the above technical objectives, the present invention provides a flexible zinc electrowinning method suitable for green electricity supply, which uses a zinc sulfate solution containing a weakly solvating additive as the electrolyte and adopts stepwise current density jump electrodeposition; the stepwise current density jump electrodeposition refers to:

[0008] When it is the peak period of green electricity supply, that is, when the power ratio ≥ 80%, constant high current density electrowinning is adopted; when it is the stable period of green electricity supply, that is, when the power ratio > 50% and < 80%, constant medium current density electrowinning is adopted; when it is the low period of green electricity supply, that is, when the power ratio ≤ 50%, constant low current density electrowinning is adopted; and when switching between the peak period of green electricity supply, the stable period of green electricity supply and the low period of green electricity supply, gradient current density electrowinning is adopted; where the power ratio is the ratio of the actual power generation of green electricity to the installed capacity of green electricity.

[0009] The key to the technical solution of the present invention lies in the synergistic effect of the electrolyte and stepwise current density jump electrodeposition to achieve uniform deposition of zinc while reducing energy consumption. Specifically, the present invention first adds a weakly solvating additive to the electrolyte. Different from the electrolytes used in existing zinc ion batteries, the weakly solvating additive of the present invention does not enter the solvation shell of zinc ions to directly participate in crystal plane growth, but changes the elementary structure in the electrolyte, including hydrogen bond structure and Zn 2+The solvation structure is thus used to regulate the competitive behavior of hydrogen and zinc on the electrode surface during the electrodeposition process. While suppressing the activity of hydrogen and broadening the electrochemical stability window of the electrolyte, it promotes the rapid desolvation of solvated zinc ions on the electrode surface, thereby improving the kinetic behavior of zinc electrodeposition and promoting its uniform deposition. More importantly, due to the weak solvation effect of the additive, the stability of the solvation structure of zinc ions at different current densities can be maintained, achieving stability under the high volatility of the electrowinning process caused by the uncertainty and volatility of green power supply. This principle of regulating the liquid-phase structure effectively solves the problem of slow deposition kinetics and severe cathode polarization caused by the adsorption and other interactions between traditional additives and the electrode, making it difficult to achieve the synergy of efficient hydrogen inhibition and rapid zinc deposition at high current densities.

[0010] On the other hand, according to the differences in power supply capabilities during the direct supply of green power, the present invention is divided into three time periods, and the current density is adjusted accordingly to ensure the stable and efficient operation of zinc electrowinning. During the peak period of green power supply, the power supply capacity is strong, and high current density can be used for electrowinning during this period to improve the utilization rate of green power; while during the low period, a lower current density can be used to alleviate problems such as reduced production capacity caused by insufficient power supply; during the stable period of green power supply, a medium current density can be used to balance the power supply / consumption balance. At the same time, the inventors found that a gradual change in current density during the mutual switching between the peak period of green power supply, the stable period of green power supply, and the low period of green power supply is crucial for the uniformity of zinc deposition. If the current density is switched instantaneously, it will exacerbate the non-uniformity of ion concentration at the electrolyte and cathode interface, and cause uneven distribution of the electrode electric field. Zinc ions are prone to tip discharge and non-uniform deposition, promoting side reactions, reducing the current efficiency, and increasing energy consumption. The present invention adopts a switching method of gradual change in current density, which can provide sufficient buffer time to maintain the stable and efficient operation of electrowinning. In addition, if the same constant current density is used during the peak period of green power supply, the stable period of green power supply, and the low period of green power supply, the zinc electrowinning conditions will deteriorate severely, making it difficult to maintain the efficient operation of the zinc electrowinning process. For example, if a high current density is used in all three periods, it will be difficult to maintain the power demand during the stable and low periods of green power supply, resulting in some electrolytic cells shutting down to maintain the normal operation of a small number of electrolytic cells; while if a low current density is used uniformly, it will cause waste of electric energy during the peak period of green power supply, increasing costs.

[0011] As a preferred solution, the weak solvation additive is an organic small molecule that is soluble in aqueous solution and acid-resistant with a Gutmann donor value lower than 20 kcal / mol.

[0012] In the zinc sulfate solution used in the present invention, the solvent is water, and the DN value of water molecules is 18 kcal / mol. In the zinc sulfate solution, zinc ions usually form Zn(H2O)6 2+ solvation structure. Organic substances with a DN value much higher than that of water molecules have a stronger interaction with zinc ions, will form a competitive relationship with water molecules, and participate in the solvation behavior of zinc ions. This relationship with stronger coordination has a high desolvation energy barrier during the electrodeposition process, hinders the discharge of zinc ions, and thus greatly reduces the current efficiency. The addition of this additive with weak solvation effect, due to the hydrogen bond formed with water and being insufficient to participate in the zinc ion solvation structure, under this "pulling" effect, the radius of the zinc ion solvation shell increases, weakening the interaction between zinc ions and solvated water, so that water molecules break away from the zinc ion solvation shell, accelerating the reaction kinetics. And the hydrogen bond can greatly reduce the reaction activity of hydrogen, thus inhibiting the occurrence of the hydrogen evolution side reaction.

[0013] As a preferred solution, the zinc sulfate solution is derived from the zinc sulfate solution generated in the zinc hydrometallurgy process, with a pH less than 2. In the zinc sulfate solution of the present invention, there is also a large amount of sulfuric acid and the pH is relatively low. Therefore, the selected organic small molecules also need to have strong acid resistance.

[0014] As a preferred solution, the organic small molecule is at least one of acetonitrile, acetone, diethylene glycol dimethyl ether, methanol, tetrahydrofuran, sulfolane, 2-butanone, formic acid, butanol, and ethylene glycol dimethyl ether. Further preferably, the organic small molecule is at least one of acetonitrile, acetone, sulfolane, and ethylene glycol dimethyl ether.

[0015] As a preferred solution, the molar ratio of the weak solvation additive to zinc sulfate is 1:(0.5 - 4). In the present invention, if the amount of the weak solvation additive is too small, the influence of the additive on the zinc ion solvation structure and hydrogen bond structure is small, and it is difficult to exert the corresponding effect. When its amount is too large, the additive directly participates in the zinc ion solvation structure due to excessive amount, thereby increasing the desolvation energy of zinc ions and reducing the current efficiency; at the same time, too much additive will increase the viscosity of the electrolyte, reduce the ionic conductivity, aggravate the electrode polarization, and also increase the energy consumption. Therefore, it is necessary to strictly control the amount of the weak solvation additive.

[0016] As a preferred solution, the current density used for the constant high current density electrowinning is 800 - 1000 A / m 2 and the current density used for the constant medium current density electrowinning is greater than 500 and less than 800 A / m 2 and the current density used for the constant low current density electrowinning is 300 - 500 A / m 2In the present invention, the control of the current density in the three time periods has a direct impact on both the reduction of energy consumption and the uniformity of zinc deposition. Within the selected current density range of the present invention, lower energy consumption and higher uniformity are further ensured.

[0017] As a preferred embodiment, the gradient current density electrowinning switches the current density at an increasing or decreasing rate of 30 - 80 A / (m 2 ·min). When the current switching rate is lower than 30 A / (m 2 ·min), the continuous fluctuation of the current will cause instability on the cathode surface, severe polarization, and increased power consumption. When the current switching rate is higher than 80 A / (m 2 ·min), a relatively high temperature difference and concentration difference will be generated on the electrode surface due to the rapid switching of the current density, especially more severe during the current increasing process, which will cause the reverse dissolution of the product, reducing the current efficiency and the quality of the cathode product.

[0018] As a preferred embodiment, during the electrowinning process, each electrowinning cycle starts with constant high current density electrowinning. Since the overpotential of hydrogen evolution is high at high current density, and with the action of the weak solvation additive, the deposition of zinc is more uniform, which can provide a uniform and flat deposition substrate, thus providing a stable working basis for the subsequent deposition process.

[0019] As a preferred embodiment, the electrolyte adopts a continuous circulation mode in the electrolytic cell.

[0020] As a preferred embodiment, when the current density is 800 - 1000 A / m 2 , the circulation flow rate of the electrolyte is 1.3 - 1.7 m / s; when the current density is greater than 500 and less than 800 A / m 2 , the circulation flow rate of the electrolyte is 0.8 - 1.3 m / s; when the current density is 300 - 500 A / m 2 , the circulation flow rate of the electrolyte is 0.4 - 0.8 m / s. In the present invention, the circulation flow rate of the electrolyte is selected according to the current density mainly because at constant high current density, the rapid discharge of zinc ions is likely to generate an obvious concentration difference on the electrode surface, causing severe concentration polarization and increasing energy consumption. A relatively fast circulation flow rate can quickly replenish zinc ions to reduce concentration polarization. While at medium and low current densities, the formation process of the concentration difference is slower, and the circulation flow rate can be reduced to ensure low energy consumption during the electrowinning process.

[0021] As a preferred embodiment, in the continuous circulation mode, a weak solvation additive needs to be continuously added to maintain a concentration of 0.5 - 2 mol / L, and the addition amount is 0.8 - 1.5 wt% of the electrolyte circulation volume.

[0022] As a preferred embodiment, the electrolysis method is cycled according to the following system, and each electrolysis cycle starts from constant high current density electrolysis. Each electrolysis cycle is: (1) when the power ratio is ≥80%, constant high current density electrolysis is adopted; (2) when the power ratio is greater than 50% and less than 80%, constant medium current density electrolysis is adopted; (3) when the power ratio is ≤50%, constant low current density electrolysis is adopted; (4) when the power ratio becomes ≥80%, return to step (1).

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention uses a zinc sulfate solution containing a weak solvating additive as an electrolyte, utilizes the hydrogen bonding effect between the additive and water molecules, but is insufficient to participate in the solvation structure of zinc ions, weakens the interaction between zinc ions and solvated water, and thus causes water molecules to separate from the solvation shell of zinc ions, thereby inhibiting the hydrogen evolution side reaction and accelerating the desolvation process of zinc on the electrode surface, and improving the stability of the cathode during zinc electrolysis with fluctuating green electricity supply, and adopts a time-divided current density jump electrolysis process to save energy consumption while greatly improving the uniformity of zinc deposition.

[0025] (2) Electrodeposition of zinc under the condition of direct supply of green electricity greatly reduces carbon emissions during the zinc smelting process and promotes the green and low-carbon transformation of zinc smelting technology.

[0026] (3) Under the synergistic effect of weak solvating additives and time-phase current density jump electrolysis, the electrolysis current efficiency can be increased to 90-95%, and the energy consumption can be reduced to 2800-3000 kWh / t.

[0027] (4) The low-energy-consumption flexible electrowinning method provided by the present invention is applicable to the electrochemical extraction of metals in different aqueous solutions, and can also be applied to the fields of electrolytic refining, electroplating, etc. of metals such as copper and lead, and has a wide range of applications.

[0028] (5) The present invention divides the power supply capacity into three time periods according to the difference in green electricity direct supply, and adjusts the current density accordingly to ensure stable and efficient operation of zinc electrolysis, which greatly reduces energy consumption. The switching of the three time periods adopts a gradual current density switching method, which provides sufficient buffer time, maintains stable and efficient operation of electrolysis and ensures the uniformity of electrodeposition. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a picture of the zinc product obtained in Example 1.

[0030] Figure 2 This is a physical picture of the zinc product obtained in Comparative Example 1.

[0031] Figure 3 It is a physical picture of the zinc product obtained in Comparative Example 2.

[0032] Figure 4 It is a physical picture of the zinc product obtained in Comparative Example 3.

[0033] Figure 5 It is a physical picture of the zinc product obtained in Comparative Example 4.

[0034] Figure 6 It is a physical picture of the zinc product obtained in Comparative Example 5.

[0035] Figure 7 It is a physical picture of the zinc product obtained in Comparative Example 6.

[0036] Figure 8 It is a physical picture of the zinc product obtained in Example 2. Detailed implementation manners

[0037] For the convenience of understanding the present invention, the present invention will be described in more comprehensive and detailed manner below in combination with preferred embodiments, but the protection scope of the present invention is not limited to the following specific embodiments.

[0038] Unless otherwise defined, all professional terms used hereinafter have the same meanings as those commonly understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the protection scope of the present invention.

[0039] Unless otherwise specified, various reagents and raw materials used in the present invention are all commercially available products or products that can be prepared by known methods.

[0040] During the electrowinning processes of the embodiments and comparative examples of the present invention, the switching rate of the current density is decreasing when switching from a higher current density section to a lower current density section, and increasing when switching from a lower current density section to a higher current density section. Among them, the power ratio is the ratio of the actual power generation of green power to the installed capacity of green power.

[0041] Example 1

[0042] Prepare Zn 2+ with a concentration of 50 g / L and concentrated sulfuric acid with a concentration of 150 g / L, and prepare a zinc sulfate solution according to a molar ratio of acetonitrile to zinc sulfate of 1:1 for standby as the electrolyte. Use a rolled aluminum plate as the cathode and a lead-silver alloy as the anode, and the effective areas of the cathode / anode are both 1 cm 2 , the pole distance is 2 cm, the electrolyte temperature is 40 °C, start running from constant medium current density electrowinning and carry out electrodeposition according to the following regime: (1) When the power ratio is 70%, electrodeposit at 700 A / m 2 for 1 h, and the electrolyte circulation flow rate is 1.0 m / s; (2) When the power ratio is 90%, at 900 A / m2 Perform electrodeposition for 1 h with the electrolyte circulation flow rate of 1.5 m / s; (3) At a power ratio of 40%, at 400 A / m 2 Perform electrodeposition for 1 h with the electrolyte circulation flow rate of 0.5 m / s. Among them, the switching rate of the current density is 50 A / (m 2 ·min), and acetonitrile with a concentration of 1.0 mol / L is continuously added at 0.8 wt% of the electrolyte circulation volume.

[0043] The results show that the current efficiency of zinc electrowinning is 92.58%, and the energy consumption is 2729.8 kWh / t. Figure 1 Figure 10 is a physical diagram of the zinc product obtained in Example 1. It can be observed that the zinc surface is uniform, flat, and easy to peel off from the cathode.

[0044] Comparative Example 1

[0045] This comparative example is basically the same as the steps and conditions of Example 1, except that acetonitrile is not added.

[0046] The results show that the current efficiency of zinc electrowinning is 86.73%, and the energy consumption is 3185.4 kWh / t. Figure 2 Figure 21 is a physical diagram of the zinc product obtained in Comparative Example 1. It can be observed that the zinc surface is uneven, and the deposits at the edges are loose, porous, extremely uneven, and the product quality is poor.

[0047] Comparative Example 2

[0048] This comparative example is basically the same as the steps and conditions of Example 1, except that the molar ratio of acetonitrile to zinc sulfate is 3:1.

[0049] The results show that the current efficiency of zinc electrowinning is 88.33%, and the energy consumption is 3091.1 kWh / t. Figure 3 Figure 32 is a physical diagram of the zinc product obtained in Comparative Example 2. It can be observed that the zinc surface is deposited evenly, but compared with the product obtained in Example 1, it is thinner. Excessive additives instead hinder zinc deposition and increase energy consumption.

[0050] Comparative Example 3

[0051] This comparative example is basically the same as the steps and conditions of Example 1, except that the molar ratio of acetonitrile to zinc sulfate is 1:8.

[0052] The results show that the current efficiency of zinc electrowinning is 87.94%, and the energy consumption is 3176.2 kWh / t. Figure 4 Figure 43 is a physical diagram of the zinc product obtained in Comparative Example 3. It can be observed that the amount of additive is small, the effect is limited, the deposition at the edges is uneven, the surface deposition is uneven, and corrosion pits appear.

[0053] From the result comparison of Comparative Examples 1-3 and Example 1, it can be seen that the acetonitrile in the present invention and its molar ratio with zinc sulfate need to be strictly regulated. Otherwise, the purpose of inhibiting the hydrogen evolution side reaction and improving the zinc deposition morphology cannot be achieved, making it difficult to increase the current efficiency while reducing the energy consumption.

[0054] Comparative Example 4

[0055] This comparative example is basically the same as Example 1 in terms of steps and conditions, except that the additive is dimethyl sulfoxide (DN value is 29.8 kcal / mol).

[0056] The results show that the current efficiency of zinc electrowinning is 74.17%, and the energy consumption is 3513.97 kWh / t. Figure 5 Fig. is the physical picture of the zinc product obtained in Comparative Example 4. It can be observed that the deposition morphology is uniform, but the deposit is less and extremely difficult to strip from the cathode.

[0057] From the result comparison of Comparative Example 4, Comparative Example 1 and Example 1, it can be seen that the DN value of the additive has a key influence on zinc electrowinning. An additive with an excessive DN value will instead reduce the current efficiency and increase the energy consumption.

[0058] Comparative Example 5

[0059] This comparative example is basically the same as Example 1 in terms of steps and conditions, except that the electrodeposition is carried out at a current density of 900 A / m 2 The results show that the current efficiency of zinc electrowinning is 83.42%, and the energy consumption is 3372.9 kWh / t. Figure 6 Fig. is the physical picture of the zinc product obtained in Comparative Example 5. It can be observed that the surface of the deposition product is uneven and there are many corrosion pits.

[0060] Comparative Example 6

[0061] This comparative example is basically the same as Example 1 in terms of steps and conditions, except that the electrodeposition is carried out at a current density of 400 A / m 2 The results show that the current efficiency of zinc electrowinning is 79.55%, and the energy consumption is 3267.4 kWh / t.

[0062] The results show that the current efficiency of zinc electrowinning is 79.55%, and the energy consumption is 3267.4 kWh / t. Figure 7 Fig. is the physical picture of the zinc product obtained in Comparative Example 6. It can be observed that although the deposition layer is relatively smooth, the deposition layer is thin and difficult to strip from the cathode.

[0063] From the result comparison of Comparative Example 5, Comparative Example 6 and Example 1, it can be seen that the change of the green power supply period needs to match an appropriate current density. Otherwise, it is difficult to obtain a high current efficiency and low energy consumption while ensuring the quality of the deposition product.

[0064] Example 2

[0065] The steps and conditions of this embodiment are basically the same as those of embodiment 1, except that the electrodeposition starts from a constant low current density, specifically: (1) when the power ratio is 40%, at 400 A / m 2 Electrodeposition was performed for 1 h at a circulating flow rate of 0.5 m / s; (2) at a power ratio of 70%, at 700 A / m 2 Electrodeposition was performed for 1 h at a circulating flow rate of 1.0 m / s; (3) at a power ratio of 90%, at 900 A / m 2 The electrodeposition was carried out for 1 h with the electrolyte circulation flow rate being 1.5 m / s.

[0066] The results show that the zinc electrodeposition current efficiency is 89.57% and the energy consumption is 2836.2 kWh / t. Figure 8 This is a physical picture of the zinc product obtained in Example 2. Since it finally stays at a high current density, zinc dendrites can be observed on the surface of the product, and the surface deposition is not as uniform as in Example 1.

[0067] Comparative Example 7

[0068] The steps and conditions of this comparative example are basically the same as those of Example 1, except that the current change is instantaneous switching.

[0069] The results show that the zinc electrodeposition current efficiency is 87.24% and the energy consumption is 3097.6 kWh / t.

[0070] From the comparison of the results of Comparative Example 7 and Example 1, it can be seen that the current switching state will affect the occurrence of the hydrogen evolution side reaction, thereby reducing the current efficiency and increasing the energy consumption.

[0071] Comparative Example 8

[0072] The steps and conditions of this comparative example are basically the same as those of Example 1, except that acetonitrile with a concentration of 1.0 mol / L is continuously added at 2.0 wt% of the circulating amount of the electrolyte.

[0073] The results show that the zinc electrodeposition current efficiency is 83.17% and the energy consumption is 3173.4 kWh / t.

[0074] From the comparison of the results of Comparative Example 8 and Example 1, it can be seen that excessive supplementation of additives during the electrolyte circulation process causes an increase in the concentration of additives in the electrolytic cell, which in turn reduces the current efficiency and increases energy consumption.

[0075] Example 3

[0076] Configuring Zn 2+ The concentration is 80g / L, the concentration of concentrated sulfuric acid is 120g / L, and additives are added according to the molar ratio of acetone and zinc sulfate of 1:2.4 as electrolyte. The rolled aluminum plate is used as the cathode and the lead-silver alloy is used as the anode. The effective area of ​​the cathode and the anode is 2cm2 , the pole pitch is 2 cm, the electrolyte temperature is 40 °C, starting from constant high current density electrowinning and performing electrodeposition according to the following regime: (1) When the power ratio is 85%, at 1000 A / m 2 perform electrodeposition for 3 h, and the electrolyte circulation flow rate is 1.3 m / s; (2) When the power ratio is 75%, at 780 A / m 2 perform electrodeposition for 2 h, and the electrolyte circulation flow rate is 0.8 m / s; (3) When the power ratio is 40%, at 300 A / m 2 perform electrodeposition for 1 h, and the electrolyte circulation flow rate is 0.4 m / s. Among them, the switching rate of the current density is 30 A / (m 2 ·min), and acetone with a concentration of 0.5 mol / L is continuously added at 1.0 wt% of the electrolyte circulation volume.

[0077] The results show that the current efficiency of zinc electrowinning is 93.04%, and the energy consumption is 2699.5 kWh / t.

[0078] Comparative Example 9

[0079] This comparative example is basically the same as the steps and conditions of Example 3, except that acetone is not added.

[0080] The results show that the current efficiency of zinc electrowinning is 87.25%, and the energy consumption is 3357.9 kWh / t.

[0081] Example 4

[0082] Prepare Zn 2+ with a concentration of 80 g / L and concentrated sulfuric acid with a concentration of 120 g / L as the electrolyte for standby, and add additives according to a molar ratio of acetone to zinc sulfate of 5:3. Use a rolled aluminum plate as the cathode and a lead-silver alloy as the anode, and the effective areas of the cathode / anode are both 2 cm 2 , the pole pitch is 2 cm, the electrolyte temperature is 40 °C, starting from constant high current density electrowinning and performing electrodeposition according to the following regime: (1) When the power ratio is 93%, at 850 A / m 2 perform electrodeposition for 4 h, and the electrolyte circulation flow rate is 1.7 m / s; (3) When the power ratio is 78%, at 650 A / m 2 perform electrodeposition for 5 h, and the electrolyte circulation flow rate is 1.1 m / s; (2) When the power ratio is 50%, at 370 A / m 2 perform electrodeposition for 3 h, and the electrolyte circulation flow rate is 0.4 m / s. Among them, the switching rate of the current density is 70 A / (m 2 ·min), and sulfolane with a concentration of 2.0 mol / L is continuously added at 1.5 wt% of the electrolyte circulation volume.

[0083] The results show that the current efficiency of zinc electrowinning is 92.74%, and the energy consumption is 2817.6 kWh / t.

[0084] Comparative Example 10

[0085] This comparative example is basically the same as the steps and conditions of Example 4, except that sulfolane is not added.

[0086] The results show that the current efficiency of zinc electrowinning is 86.74%, and the energy consumption is 3304.3 kWh / t.

[0087] Example 5

[0088] Configure Zn 2+ with a concentration of 50 g / L, concentrated sulfuric acid with a concentration of 150 g / L, and prepare a zinc sulfate solution according to a molar ratio of acetonitrile to zinc sulfate of 1:2 as the electrolyte for standby. Use a rolled aluminum plate as the cathode and a lead-silver alloy as the anode, with the effective area of the cathode / anode both being 1 cm 2 , the electrode distance is 2 cm, the electrolyte temperature is 40 °C, and electro-deposition is carried out according to the following regime. Each electrowinning cycle starts with constant high current density electrowinning. Each electrowinning cycle is: (1) at a power ratio of 90%, electro-deposit at 900 A / m 2 for 3 h, and the electrolyte circulation flow rate is 1.5 m / s; (2) at a power ratio of 70%, electro-deposit at 700 A / m 2 for 5 h, and the electrolyte circulation flow rate is 1.0 m / s; (3) at a power ratio of 40%, electro-deposit at 400 A / m 2 for 2 h, and the electrolyte circulation flow rate is 0.5 m / s; (4) when the power ratio becomes 90%, return to step (1). Cycle 3 cycles according to this regime. Among them, the switching rate of the current density is 50 A / (m 2 ·min), and acetonitrile with a concentration of 1.0 mol / L is continuously added at 0.8 wt% of the electrolyte circulation volume.

[0089] The results show that the current efficiency of zinc electrowinning is 92.61%, and the energy consumption is 2839.7 kWh / t.

Claims

1. A flexible zinc electrowinning method adapted to green power supply, characterized in that: Using a zinc sulfate solution containing a weakly solvating additive as the electrolyte, electro-deposition is carried out with a stepwise jump in current density; the stepwise jump in current density electro-deposition means that: During the peak period of green power supply, that is, when the power ratio ≥ 80%, constant high current density electro-deposition is used; during the stable period of green power supply, that is, when the power ratio > 50% and < 80%, constant medium current density electro-deposition is used; during the low period of green power supply, that is, when the power ratio ≤ 50%, constant low current density electro-deposition is used; and when switching between the peak period of green power supply, the stable period of green power supply, and the low period of green power supply, gradient current density electro-deposition is used; Among them, the power ratio is the ratio of the actual power generation of green power to the installed capacity of green power.

2. A flexible zinc electro-deposition method adapted to green power supply according to claim 1, characterized in that: The weakly solvating additive is an organic small molecule that is soluble in aqueous solution and has acid resistance with a Gutmann donor value lower than 20 kcal / mol; The zinc sulfate solution is derived from the zinc sulfate solution generated in the zinc hydrometallurgy process, and the pH is less than 2.

3. A flexible zinc electrowinning method adapted to green power supply according to claim 2, characterized in that: The organic small molecule is at least one of acetonitrile, acetone, diethylene glycol dimethyl ether, methanol, tetrahydrofuran, sulfolane, 2-butanone, formic acid, butanol, and ethylene glycol dimethyl ether.

4. A flexible zinc electrowinning method adapted to green power supply according to claim 2 or 3, characterized in that: The molar ratio of the weakly solvating additive to zinc sulfate is 1:(0.5 - 4).

5. A flexible zinc electrowinning method adapted to green power supply according to claim 1, characterized in that: The current density used in the constant high current density electrowinning is 800 - 1000 A / m 2 , and the current density used in the constant medium current density electrowinning is greater than 500 and less than 800 A / m 2 , and the current density used in the constant low current density electrowinning is 300 - 500 A / m 2 .

6. A flexible zinc electrowinning method adapted to green power supply according to claim 1 or 5, characterized in that: The gradient current density electrowinning switches the current density at an increasing or decreasing rate of 30 to 80 A / (m 2 ·min).

7. A flexible zinc electrowinning method adapted to green power supply according to claim 1, characterized in that: The electrolyte adopts a continuous circulation mode in the electrolytic cell.

8. A flexible zinc electrowinning method adapted to green power supply according to claim 5, characterized in that: When the current density is 800 - 1000 A / m 2 , the circulating flow rate of the electrolyte is 1.3 - 1.7 m / s; when the current density is greater than 500 and less than 800 A / m 2 , the circulating flow rate of the electrolyte is 0.8 - 1.3 m / s; When the current density is 300 - 500 A / m 2 , the circulating flow rate of the electrolyte is 0.4 - 0.8 m / s.

9. A flexible zinc electrowinning method adapted to green power supply according to claim 7, characterized in that: In the continuous circulation mode, a weakly solvating additive needs to be continuously added to maintain a concentration of 0.5 - 2 mol / L, and the added amount is 0.8 - 1.5 wt% of the electrolyte circulation volume.

10. A flexible zinc electrowinning method adapted to green power supply according to claim 1, characterized in that: The electro-deposition method is cycled according to the following regime. Each electro-deposition cycle starts with constant high current density electro-deposition. Each electro-deposition cycle is: (1) When the power ratio ≥ 80%, constant high current density electro-deposition is used; (2) When the power ratio is greater than 50% and less than 80%, constant medium current density electro-deposition is used; (3) When the power ratio ≤ 50%, constant low current density electro-deposition is used; (4) When the power ratio becomes ≥ 80%, return to step (1).

Citation Information

Patent Citations

  • Process for reducing cathode zinc direct-current current unit loss in zinc wet method smelting for processing high mixed ore

    CN105937040A

  • Method for reducing zinc electrodeposition direct current power consumption

    CN117779112A